(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article discusses the use of French texts in teaching French to first-year students. The author highlights several key advantages of this approach, including the development of reading, comprehension, and speaking skills in the original language, as well as improvement in vocabulary and grammar skills. Possible difficulties that students may encounter when working with French texts at the initial stage of learning are also discussed. A number of methods and techniques are proposed to help overcome these difficulties and successfully utilize French texts in the learning process.